The Role of Islamic Microfinance for Poverty Alleviation in Mogadishu, Somalia: An Exploratory Study - Elmi Xalane, Mohamed Abdi; Che Mohd Salleh, Marhanum (New Millennium Discoveries, 2019)
This research aims to investigate the current practice of Islamic microfinance in Mogadishu, Somalia and to examine the effectiveness of Islamic microfinance institutions in Somalia on poverty reduction. In total, 65 microfinance recipients participated in the survey. This research adopts a quantitative methodology, using a survey and descriptive analysis. Findings show that the current practice of Islamic microfinance in Mogadishu is serving the poor and that these microfinance activities are effective in terms of obtaining loans, enhancement of standards of living and usefulness of the system. Nonetheless, there is a low level of awareness among the locals regarding the availability of Islamic microfinance.